(untitled) (Journal of Event, Tourism and Hospitality Studies, 2025)
This study investigates how environmental, social, and economic sustainability initiatives influence participant satisfaction and experience at the Penang George Town Festival (PGTF), a leading cultural heritage event in Malaysia. Guided by Sustainable Development Theory and the Triple Bottom Line (TBL) framework, the research adopts a quantitative, participant-centered approach to evaluate how attendees perceive and respond to sustainability efforts. Using structured surveys, data were collected from 150 participants and analysed through descriptive statistics, reliability testing, and Pearson correlation analysis. The findings reveal that all three sustainability dimensions significantly affect participant satisfaction, with social sustainability notably cultural inclusivity and community engagement emerging as the strongest predictor (r = 0.68, p < .001). Environmental (r = 0.61) and economic (r = 0.54) sustainability also show meaningful positive impacts. These results affirm that sustainability practices are not only operational imperatives but also critical experiential drivers in cultural events. The study contributes to the limited empirical evidence from Southeast Asian contexts and highlights the need for holistic, multidimensional sustainability strategies in festival planning. The insights derived are particularly valuable for festival organizers, destination managers, cultural policy-makers, and local community stakeholders seeking to enhance event quality, promote inclusive development, and strengthen tourism resilience.